Australian elite sport coaches` mental health literacy of eating disorders, orthorexia, and muscle dysmorphia in athletes: A qualitative study - Mitchell, J.; Tilbrook, M.; Kiropoulos, L.; Krug, I. (Body Image, 2024)
Athletes have an increased risk of developing eating disorders (EDs) compared to non-athletes. Coaches are in a unique position to identify symptoms and promote timely support; however, research has not yet explored coaches` mental health literacy about DSM-5 EDs and related orthorexia and muscle dysmorphia conditions in elite athletes. Eighteen Australian elite sport coaches from aesthetic, weight-class, and endurance sports participated in individual semi-structured interviews to investigate their mental health literacy of EDs and related conditions. Four themes emerged from the data. Theme 1 (knowledge of EDs and related conditions) highlighted coaches` awareness of maladaptive perfectionism as a key risk factor, limited awareness of EDs without observable weight loss, and conceptualisation of EDs as a nutritional issue. Theme 2 (facilitators to managing EDs) highlighted the helpfulness of building trust with athletes, accessing support staff, emphasising body functionality, and lived experience. Theme 3 (barriers to managing EDs) highlighted coaches` challenges with communicating about body image, responding to denial, and funding constraints. Theme 4 (future ED education and training) highlighted coaches` desire for in-person, interactive training and to support junior-level coaches. These findings may assist in developing tailored educational resources to improve coaches` ability to identify and manage eating-related concerns in athletes.